Onion (Allium cepa L.) and Drought: Current Situation and Perspectives - Oladé Charles Sansan; Vincent Ezin; Mathieu Anatole Tele Ayenan; Ifagbémi Bienvenue Chabi; Hubert Adoukonou-Sagbadja; Aliou Saïdou; Adam Ahanchede (Scientifica)
Onions (Allium cepa L.) are the second most commonly produced and consumed vegetable worldwide due to their economic, nutritional, and medicinal benefits. However, drought hinders vegetative growth, lowers yields and bulb quality, reduces photosynthetic activity, and alters the onion plant’s metabolism. This review provides a summary of global research on the impact of drought on onions. It specifically seeks to shed light on aspects that remain unclear and generate research avenues. Relevant scientific articles were sourced from the AGORA database, Web of Science (WoS), and search engines such as Google Scholar, Scopus, MEDLINE/PubMed, and SCImago to achieve this objective. A total of 117 scientific articles and documents related to onion and drought were critically examined. The review revealed agromorphological, physiological, biochemical, and genomic studies depicting factors that contribute to drought tolerance in onion genotypes. However, there was little research on the physiological, biochemical, and genetic characteristics of drought tolerance in onions, which need to be deepened to establish its adaptation mechanisms. Understanding the mechanisms of onion response to water stress will contribute to fast-tracking the development of drought-tolerant genotypes and optimize onion production. Future research should be more focused on investigating onion drought tolerance mechanisms and structural and functional genomics and identifying genes responsible for onion drought tolerance.